Oxygen isotope-based evidence for stepwise climate cooling aligns with the tripartite division of the Ordovician - Zhang, Zhutong; Wu, Rongchang; Lehnert, Oliver; Calner, Mikael; Rasmussen, Christian M.Ø.; Tang, Guo-Qiang; Li, Xian-Hua (Global and Planetary Change, 2025)
The Ordovician Period includes two major macroevolutionary events: the Great Ordovician Biodiversification Event (GOBE) and the Late Ordovician Mass Extinction (LOME), alongside a fundamental climate transition from a greenhouse to an icehouse state. Although both biological events occurred during relatively short-term global cooling conditions, their starkly contrasting biotic responses remain poorly understood. Here, we present high-resolution conodont apatite δ18O records from Sweden combined with global data to reconstruct a stepwise seawater temperature decline from ∼43.7 °C in the Floian to ∼25.1 °C by the late Katian. Three discrete periods of global cooling occurred at 471.2–469 Ma (CE1), 460.2–456.1 Ma (CE2), and 443–442.4 Ma (CE3), with rates of 5–6 °C/Myr, 2–3 °C/Myr, and > 15 °C/Myr. Hence, the three steps coincide with the tri-partite Ordovician series boundaries. CE1 aligns with the initiation of the GOBE, while CE3 coincides with the LOME. This indicates that cooling regulated both the GOBE and the LOME, framing possible end-member states of organismal homeostasis. During CE1, the transition from warm to temperate conditions occurred at a relatively moderate cooling rate, reaching an optimal window for promoting biodiversity growth. In contrast, during CE3, the shift from temperate to cold conditions involved a more rapid cooling rate, exceeding organismal thresholds and negatively impacting biodiversity. These three cooling episodes coincide with a decline in seawater 87Sr/86Sr suggesting enhanced weathering and CO2 drawdown, further reinforced by the expansion of marine algae and land vegetatio
Keywords: Conodont apatite; SIMS; Climate change; Ordovician biodiversity change; Metazoan homeostatic optimum; Baltica